Evolutionary Patterns of Maternal Recognition of Pregnancy and Implantation in Eutherian Mammals - Braz, Henrique Bartolomeu; Barreto, Rodrigo da Silva Nunes [UNESP]; Silva-Júnior, Leandro Norberto da; Horvath-Pereira, Bianca de Oliveira; Silva, Thamires Santos da; Silva, Mônica Duarte da; Acuña, Francisco; Miglino, Maria Angelica (MDPI, 2024)
The implantation of the embryo into the maternal endometrium is a complex process associated with the evolution of viviparity and placentation in mammals. In this review, we provide an overview of maternal recognition of pregnancy signals and implantation modes in eutherians, focusing on their diverse mechanisms and evolutionary patterns. Different pregnancy recognition signals and implantation modes have evolved in eutherian mammals, reflecting the remarkable diversity of specializations in mammals following the evolution of viviparity. Superficial implantation is the ancestral implantation mode in Eutheria and its major clades. The other modes, secondary, partially, and primary interstitial implantation have each independently evolved multiple times in the evolutionary history of eutherians. Although significant progress has been made in understanding pregnancy recognition signals and implantation modes, there is still much to uncover. Rodents and chiropterans (especially Phyllostomidae) offer valuable opportunities for studying the transitions among implantation modes, but data is still scarce for these diverse orders. Further research should focus on unstudied taxa so we can establish robust patterns of evolutionary changes in pregnancy recognition signaling and implantation modes.
Keywords: evolution; implantation; pregnancy